Pregnancy with Myasthenia Gravis - Ninuk Dwi ariningtyas; Laily Irfana (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTMyasthenia Gravis (MG) is a serious autoimmune disease, but now can be treated. Symptoms include weakness and fatigue in voluntary muscles caused by an autoantibody reaction to nicotinic acetylcholine receptor (AChR) at the post synapse of the neuromuscular junction. Pregnancy can affect autoimmune diseases so that pregnancy can aggravate MG disease. On the other hand it is also reported that pregnancy does not affect and can even improve MG disease. In this article, We report a 27-year-old woman who was diagnosed with myasthenia gravis that having a pregnancy. Initially she had no problems with pregnancy. Patients underwent pregnancy by taking the drug Mestinon four times daily and roborant. But entering the 33rd-34th week, the examination results showed that the pregnancy experienced oligohydramnios and Intrauterine Growth Retardation (IUGR), it was probably caused by malnutrition. Then we decided to end the patient's pregnancy with a Caesarean section. The operation went well, born to a baby boy / 2450grams / Apgar Score 5-7. Observation for one week the mother's condition continued to improve. Diplopia and weaknesses also improve. Likewise the baby showed a healthy condition. The patient was discharged while still taking MG drugs that had been previously consumed. This case report showed that pregnancy worsened MG disease, but MG did not affect pregnancy.Keywords : Pregnancy, Myasthenia Gravis